2022
DOI: 10.3390/pharmacy10010034
|View full text |Cite
|
Sign up to set email alerts
|

Improving Asthma Management: Patient–Pharmacist Partnership Program in Enhancing Therapy Adherence

Abstract: Community pharmacist interventions can assist in improving adherence in patients with asthma. The objective of the study was to assess the feasibility of patient-centered counseling using the developed asthma-specific tools to identify barriers to adherence and identify their preliminary effect on adherence barrier score and asthma control. Adult patients with persistent asthma were invited to participate in a 3-month pre–post intervention study involving community pharmacist-provided patient-centered counseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Nevertheless, there exists room for enhancement in elevating awareness about specific intervention options such as lactulose, probiotics, and laxatives, alongside mood regulation to alleviate constipation symptoms. In consideration of these outcomes, refining clinical practice involves the provision of personalized counseling and support to assuage concerns and anxieties, particularly for those experiencing heightened distress ( 33 , 34 ). Furthermore, an opportunity arises to enlighten gravid females on diverse management options, underscoring the efficacy of dietary and lifestyle adjustments, and enhancing awareness about specific interventions when warranted ( 28 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there exists room for enhancement in elevating awareness about specific intervention options such as lactulose, probiotics, and laxatives, alongside mood regulation to alleviate constipation symptoms. In consideration of these outcomes, refining clinical practice involves the provision of personalized counseling and support to assuage concerns and anxieties, particularly for those experiencing heightened distress ( 33 , 34 ). Furthermore, an opportunity arises to enlighten gravid females on diverse management options, underscoring the efficacy of dietary and lifestyle adjustments, and enhancing awareness about specific interventions when warranted ( 28 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their paper, Unni et al developed a new hierarchical model to explain medication adherence, with health literacy as the basis, and illness beliefs, medication beliefs, and self-efficacy as hierarchical steps to achieve medication adherence [ 4 ]. Makhinova and colleagues examined the medication use experience of patients with persistent asthma and the potential influence of pharmacists in improving medication adherence [ 5 ]. The study showed how pharmacists were able to reduce the treatment belief barriers of patients, which impacts their medication adherence.…”
mentioning
confidence: 99%